The role of the educational supervisor in overcoming the problems which face the teachers of the first episode in the basic learning in Damascus city schools - al-moukatren, suzan (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aims to recognize the role of the educational supervisor in overcoming the problems which face the first episode teachers of basic learning , and present some solutions which help to solve these problems and determine the differences among teachers opinions in the roles which the supervisors must do to help them in overcoming their problems according to the varieties of ‘‘sex, scientific qualification , years of experience in teaching, and the training sessions.’’ To achieve these aims, the research followed the descriptive analytic approach, A questionnaire consisted of (45) items was prepared, applied on as ample consisted of (851) teachers the first episode in Damascus schools in the year (2014-2015),The resulted showed the most problems which the role of the educational supervisor is effective are the class problems, but the role of the educational supervisor was substandard in overcoming the psychological problems. The results also showed significance statistic variances among the teachers appreciations average according to the roles which the educational supervisors perform in overcoming the problems of the first episode teachers in basic learning according to the varieties of “sex, scientific qualification, years experience in teaching, and training sessions.